PERHITUNGAN KOORDINAT (X,Y,Z) POLIGON TERTUTUP DENGAN METODE BOWDITCH PADA SPREADSHEETS EXEL - Arie Syahruddin Sibarani; Helmiati - (Jurnal APTEK, 2012)
The process count and stage a series of meridians on the work of geodetic data processing (mapping). The process is expected to have rigorous criteria, fast, and easy, both in data entry, calculation, data repair, and printing the results. . Pack with Microsoft Exel provides easiness that required by a process of calculation. This package can be used for data entry, calculation, and the improvement of data at once in one worksheet, with a format that can be customized. Likewise, if desired, printing the results can be obtained from the worksheet. In this paper are presented the way we use Exel spreadsheets to count how Bowditch closed polygon coordinates.